Simposium Serantau Sastera Islam - Simposium Serantau Sastera Islam (1992 : Universiti Brunei Darussalam) (Bandar Seri Begawan, Negara Brunei Darussalam : Dewan Bahasa dan Pustaka Brunei, 1996)
Role of Islamic literature in the development of Brunei society; papers of a symposium.
Includes bibliographical references.
In Malay
Koleksi sumbangan : Prof. Emeritus Dato' Dr. Wan Hashim Wan Teh
Keywords: Islamic literature, Malay -- Brunei -- History and criticism -- Congresses; Malay literature -- Islamic influences -- Brunei -- Congresses; Islam -- Brunei -- Congresses; Brunei -- Civilization -- Islamic influences -- Congresses